Towards sustainable yield improvement: field inoculation of soybean with Bradyrhizobium and co‑inoculation with Azospirillum in Mozambique - Chibeba, A.M.; Kyei-Boahen, S.; Fátima Guimarães, M. de; Nogueira, M.A.; Hungria, M. (Springer, 2020)
The effects of sole inoculation of soybean (Glycine max L. Merrill) with Bradyrhizobium and co-inoculation with Bradyrhizobium and Azospirillum on nodulation, plant growth and yields were investigated in the 2013/2014 and 2014/2015 cropping seasons under field conditions in Mozambique. The treatments included (1) Control (non-inoculated control, with symbiosis depending on indigenous rhizobia), (2) Urea (non-inoculated, receiving 200 kg ha−1 of N), (3) Sole inoculation with B. diazoefficiens strain USDA 110, and (4) Co-inoculation with B. diazoefficiens strain USDA 110 and A. brasilense strains Ab-V5 and Ab-V6, evaluated in a randomized complete block design with five replications. Nodule number and dry weight, shoot dry weight, biological and grain yields, grain dry weight, and harvest index were evaluated. In general, both sole inoculation and co-inoculation enhanced nodulation in relation to control. Sole inoculation increased grain yield by 22% (356 kg ha−1), the same enhancement magnitude attained under mineral N treatment, suggesting that Bradyrhizobium inoculation provides ecological and economic sustainability to the soybean crop in Mozambique or other countries with similar agro-climatic conditions. Co-inoculation did not increase grain yields in relation to neither the control nor sole inoculation, indicating that further research with adapted and high yielding soybean varieties along with effective rhizobial strains is required in Mozambique to attune the beneficial Azospirillum–plant cultivar–rhizobia interactions that have been reported in other countries for several legumes, including soybean.